NON AUTOMATICALLY EXERCISED (NAE) EUROPEAN CAPPED CALL PRICING THEORY - ., Subanar; Guritno, Suryo; S., Zanzawi; ., Abdurakhman (Journal of the Indonesian Mathematical Society, 2007)
The objective of this paper is to present a methodology for deriving Black Scholes formulae via a simple lognormal distribution approach and introduce European capped non automatically exercise (NAE) call option pricing theory.Â DOI :Â http://dx.doi.org/10.22342/jims.13.2.69.215-221